Pengaruh Self-Efficacy dan Work Engagement Terhadap Work Family Enrichment pada Perawat Perempuan di Rumah Sakit Pekanbaru - Saskia Maharani; Hijriyati Cucuani (Psychopolytan : Jurnal Psikologi, 2026)
The nursing profession has experienced an increase in numbers each year. However, married nurses tend to face an imbalance between work and family due to the dual roles they perform. Women who choose to continue working and are able to positively integrate their work and family roles are described by the concept of work–family enrichment. This study aims to examine the relationships among self-efficacy, work engagement, and work-family enrichment among female nurses at hospitals in Pekanbaru. This study used a quantitative, correlational method. The research subjects were 201 married female nurses who had worked at a hospital for at least 6 months. Data collection used the work-family enrichment scale, the generalised self-efficacy scale, and the Utrecht work engagement scale. The results of multiple linear regression showed a significant relationship between self-efficacy and work engagement with work-family enrichment (p <.001). Self-efficacy and work engagement accounted for 39.8% of work-family enrichment. Partially, work engagement correlated more highly (β = 0.372) than self-efficacy (β = 0.354) with work-family enrichment. This study emphasises the importance of developing self-efficacy and work engagement for married female nurses to improve work-family enrichment.